2004
DOI: 10.1177/088307380401900516
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Decreased Oxygenation During Focal Status Epilepticus in a Neonate With Hemimegalencephaly

Abstract: Early surgical removal of a dysplastic hemisphere appears to be beneficial for neonates with hemimegalencephaly and medically resistant seizures. We analyzed the changes in the cerebral regional oxygen saturation index in a neonate with tuberous sclerosis and right hemimegalencephaly (1) during seven episodes of right hemisphere electroencephalographic status epilepticus with and without clinical manifestations and (2) after right hemispherectomy. The cerebral regional oxygen saturation index demonstrated mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
0
9
0
3
Order By: Relevance
“…The proposed mechanism of this injury has been decreased oxygenation of the more normal hemisphere by a steal-like phenomenon [18, 19]. Alfonso et al [19], using near-infrared spectroscopy (SPECT), found bilateral decreased oxygen saturation in a 3-week-old with tuberous sclerosis and hemimegalencephaly; this was interpreted as being due to increased oxygen consumption by the abnormal brain with decreased availability of oxygen to the normal hemisphere. Soufflet et al [18] demonstrated earlier return of normal cerebral blood flow in infants who underwent early hemispherectomy compared to their counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The proposed mechanism of this injury has been decreased oxygenation of the more normal hemisphere by a steal-like phenomenon [18, 19]. Alfonso et al [19], using near-infrared spectroscopy (SPECT), found bilateral decreased oxygen saturation in a 3-week-old with tuberous sclerosis and hemimegalencephaly; this was interpreted as being due to increased oxygen consumption by the abnormal brain with decreased availability of oxygen to the normal hemisphere. Soufflet et al [18] demonstrated earlier return of normal cerebral blood flow in infants who underwent early hemispherectomy compared to their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…The intrauterine excessive fetal movement and hiccups were likely manifestations of intrauterine seizure activity [11]. Rapidly progressing clinical and EEG abnormalities raised concern for irreversible injury to the more normal-appearing right hemisphere, as a result of epileptogenic bombardment from the abnormal hemisphere [13,16,17,18,19]. The proposed mechanism of this injury has been decreased oxygenation of the more normal hemisphere by a steal-like phenomenon [18, 19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Es folgte eine Reihe von Einzelfallberichten und kleinen Fallserien mit insgesamt 13 Patienten im Alter von einem Monat bis 31 Jahren [2,33,38,42,56,92,106,116]. Die Dauer der SE lag in den Studien zwischen 6 und 42 Tagen.…”
Section: Epilepsiechirurgische Interventionenunclassified